Advances and challenges in understanding the role of the lipid raft proteome in human health. (2nd December 2018) - Mohamed, Ahmed; Robinson, Harley; Erramouspe, Pablo Joaquin; Hill, Michelle M
ABSTRACT: Introduction : Phase separation as a biophysical principle drives the formation of liquid-ordered 'lipid raft' membrane microdomains in cellular membranes, including organelles. Given the critical role of cellular membranes in both compartmentalization and signaling, clarifying the roles of membrane microdomains and their mutual regulation of/by membrane proteins is important in understanding the fundamentals of biology, and has implications for health. Areas covered : This article will consider the evidence for lateral membrane phase separation in model membranes and organellar membranes, critically evaluate the current methods for lipid raft proteomics and discuss the biomedical implications of lipid rafts. Expert commentary : Lipid raft homeostasis is perturbed in numerous chronic conditions; hence, understanding the precise roles and regulation of the lipid raft proteome is important for health and medicine. The current technical challenges in performing lipid raft proteomics can be overcome through well-controlled experimental design and careful interpretation. Together with technical developments in mass spectrometry and microscopy, our understanding of lipid raft biology and function will improve through recognition of the similarity between organelle and plasma membrane lipid rafts and considered integration of published lipid raft proteomics data.